Secularism: the basics - Berlinerblau, Jacques (The basics, 2024)
"Secularism: The Basics is a concise and engaging introduction to confusing and contradictory public discussions of secularism across the globe. In this lively and lucid book, Jacques Berlinerblau addresses why secularism is defined in so many ways and why it so ignites people's passions. In so doing, he explores the following important questions: What does secularism mean? Why should we care about this idea? What are the different types of secularism and what are their histories? What are the basic principles of political secularisms? Why are secularism and Atheism often confused? What is the relationship between secularism and LGBTQ rights? What opposition are secularisms up against? What does the future hold for a concept millennia in the making, but only really operationalized in the last century and a half? This thoroughly updated new edition includes two new chapters on African Secularisms and the importance of Mexico in the history of political secularism. With a glossary of key terms, new and updated case studies throughout, informative tables, and suggestions for further reading, the book considers key philosophical, religious, anti-religious, and post-colonial arguments around secularism. This book continues to be an ideal starting point for anyone seeking a readable introduction to the often-conflicting interpretations of one of our era's most complex and controversial ideas"--